The Grime scene: social media, music, creation and consumption - McGrath, Sean; Chamberlain, Alan; Benford, Steve (2016)
In this paper we start to explore and unpack the work of Grime music producers and performers with a focus on their attitudes, working practices and use of social media. We explore the origins of grime and describe a complex set of interactions between people and technology in order to facilitate the production and dissemination of audio content in an evolving digital climate. We explore how individuals in this space curate and collect content, with a view to reuse in the future. We also explore how grime is evolving and ways in which technology might be able to facilitate many of these processes more effectively. Finally, we explore technological issues that pertain to music production and dissemination in its current state and implications for design for future applications and contexts.